Availability of ambulance patient care reports in the emergency department. Issue 1 (14th January 2016) - Shelton, Dominick; Sinclair, Paul
Abstract: Clinical handovers of patient care among healthcare professionals is vulnerable to the loss of important clinical information. A verbal report is typically provided by paramedics and documented by emergency department (ED) triage nurses. Paramedics subsequently complete a patient care report which is submitted electronically. This emergency medical system (EMS) patient care report often contains details of paramedic assessment and management that is not all captured in the nursing triage note. EMS patient care reports are often unavailable for review by emergency physicians and nurses. Two processes occur in the distribution of EMS patient care reports. The first is an external process to the ED that is influenced by the prehospital emergency medical system and results in the report being faxed to the ED. The second process is internal to the ED that requires clerical staff to distribute the fax report to accompany patient charts. A baseline audit measured the percentage of EMS patient care reports that were available to emergency physicians at the time of initial patient assessments and showed a wide variation in the availability of EMS reports. Also measured were the time intervals from patient transfer from EMS to ED stretcher until the EMS report was received by fax (external process measure) and the time from receiving the EMS fax report until distribution to patient chart (internal process measure). These baseline measures showed a wide variation in the time it takes to receive the EMS reports by fax and to distribute reports. Improvement strategies consisted of: 1. Educating ED clerical staff about the importance of EMS reports 2. Implementing a new process to minimize ED clerical staff handling of EMS reports for nonactive ED patients 3. Elimination of the automatic retrieval of old hospital charts and their distribution for ED patients 4. Introduction of an electronic dashboard for patients arriving by ambulance to facilitate more efficient distribution of EMS reports. Implementation of change strategies did not result in a significant improvement in the percentage of EMS reports available to emergency physicians at the time of initial patient assessment. However, tracking both external and internal processes that influence EMS report availability showed the internal process time from fax report receipt to distribution significantly improved. This improvement reflected the change strategies that were all directed at improving the internal process. EMS patient care reports are more efficiently processed and distributed in the ED due to change strategies implemented that targeted the ED's internal process of EMS report distribution. The external process responsible for transmitting EMS reports to the ED is the limiting factor that prevents consistent timely access of EMS reports by emergency physicians and will require dedicated improvement strategies.